2008
DOI: 10.1007/s12032-008-9138-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, anxiety and depression in Turkish breast cancer patients and in their husbands

Abstract: The aim of the present study is to investigate anxiety and depression levels and quality of life of Turkish breast cancer patients and their husbands with Beck depression, STAI scoring system, and EORTC-QLQ-C30 quality of life scale. Fifty-five patients with breast cancer undergoing chemotherapy who applied to Dokuz Eylul University Faculty of Medicine, Department of Oncology, and their husbands were included in this study. The series of forms including the questions regarding the demographic characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 18 publications
1
22
1
3
Order By: Relevance
“…[45]. Out of 17 studies, 9 studies followed descriptive cross sectional research design [2,34,42,43,45,57,59,60,62] cross sectional comparative design was used in 2 studies [38,65] 2 studies followed longitudinal design [33, 44,54] observational cohort design was used in 2 studies [30,65] and only 1 study followed correlation design [63]. Only four studies had sample size lower than 100 [2,56].…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…[45]. Out of 17 studies, 9 studies followed descriptive cross sectional research design [2,34,42,43,45,57,59,60,62] cross sectional comparative design was used in 2 studies [38,65] 2 studies followed longitudinal design [33, 44,54] observational cohort design was used in 2 studies [30,65] and only 1 study followed correlation design [63]. Only four studies had sample size lower than 100 [2,56].…”
Section: Data Extractionmentioning
confidence: 99%
“…Two studies reported that prevalence of depression in breast cancer patients at 0-III stage ranges from 13-30% [57,65]. Prevalence of depression in breast cancer women undergoing chemotherapy is 19.1% 29% [2,45] and of anxiety is 24.1% while in women at 6 months post-chemotherapy prevalence of depression is 10% and of anxiety is 46.4% [62]. Prevalence of depression in women under follow up for breast cancer treatment is 29% while prevalence of grade I anxiety is 2.5%, grade II anxiety is 77%, grade III anxiety is 19% [34] while prevalence of depression in breast cancer women at completion of treatment is 22.2% and of anxiety is 38.4% [54].…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Du rum lu luk kay gı öl çe ği için de ğer len di ril me ya pı -lır ken her mad de için mad de nin po zi tif ya da ne gatif özel li ği ne gö re 1 (ya da -1) ile 4 (ya da -4) ara sın da bir pu an ve ril mek te olup, el de edi le cek top lam pua na 50 sa bi ti ek len mek te dir. 12 Öl çek ten el de edi len pu an lar 20 ile 80 ara sın da de ğiş mek te olup bü yük pu an yük sek kay gı se vi ye si ni, kü çük pu an dü şük kay gı se vi ye si ni be lir tir. 13 Biz de ça lış ma mız da STAI' nin du rum lu luk kay gı öl çe ği ni kul lan dık.…”
Section: Anesthesiology and Reanimationunclassified
“…In Literature, along with the many studies that analyzes the anxiety levels of patients with breast cancer in Turkey (Alacacioglu et al, 2009;Turhal et al, 2010;Dastan and Buzlu, 2011;Tasci et al, 2012) and around the world Schleife et al, 2014;Stafford et al, 2014); there are many studies that analyze the impact of non-pharmacological interventions towards patients on the anxiety and comfort level (Liu et al, 2011;Can et al, 2012;Emilsson et al, 2012;Özkorumak et al, 2012;Yavuzsen et al, 2012;Carayol et al, 2013;Halkett et al, 2013;Henderson et al, 2013;Kim et al, 2013;Serra et al, 2013;Tanrıverdi and Aydemir, 2013). However when the literature is analyzed, there could not be found a single study towards determining the comfort and anxiety levels of women that receive early stage breast cancer radiotherapy in our country.…”
Section: Introductionmentioning
confidence: 99%